DEVELOPMENT OF DIGITAL COMIC LEARNING MEDIA BASED ON SCIENTIFIC APPROACH AS CHARACTER STRENGTHENING IN 2nd GRADE OF ELEMENTARY SCHOOL - Muh Ardian Wahyudi; Linda Feni Haryati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2023)
The development of digital comic media as an effort to provide innovation and education in character education in learning material on religious diversity is based on several gaps, including: 1) students' lack of understanding of religious diversity in Indonesia, 2) lack of student understanding of tolerance, 3) The way teachers provide religious diversity material is conventional and only based on books. The purpose of this research to find out digital comic media development and implementation at SDN 2 Golong. Based on the problems that have been described, the development aims to produce valid digital comic media for grade II students of SDN 2 Golong. The development of this digital comic media used the ADDIE development model. There are 5 stages in the development process that have been carried out in this research, namely 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. The assasement of digital comic media was carried out by material experts, media experts, educators, and second grade students at SDN 2 Golong. The results of the research showed that the development of digital comic media show that the percentage obtained from material expert validators, which is 85% with a very valid category and suitable for use without improvement, the value obtained from media expert validators, is 91.25% with a very valid category and suitable for use without improvement. but there are still revisions. Furthermore, the results of the educator's trial 91% with a very valid category and suitable for use without improvement. The results of field trials were carried out with 20 students with a percentage of 88% in the very interesting category. Based on the results of the data analysis, it can be concluded that the development of digital comic media is fit and possible to used as a media learning.